PENGARUH SISTEM PENCATATAN DAN PELAPORAN TERHADAP MUTU DATA PUSKESMAS DI KOTA BANJARBARU (STUDI KASUS MENUJU PUSKESMAS TERAKREDITASI) - Armiati Armiati (An-Nadaa: Jurnal Kesehatan Masyarakat (e-Journal), 2018)
Accreditation of primary health care is important to increase the quality of service at primary health care. In Banjarbaru city, accreditation of primary health care starts in 2016 with target of 4 (four) primary health care. The importance of recording and reporting is also emphasized on the standard of primary health care accreditation that is standard 2.3.17 data and information management at puskesmas, standard 7.1 patient registration process and standard 8.4 medical record information management. The use of ICD-10 in the coding process is 62.5% using ICD-10 and 37.5% using the code on SIMPUS. The completeness of recording of medical record documents is 20% and not complete by 80%. Standardization of disease codes and the completeness of medical record documents including standard assessment of medical record information management. The purpose of research for explain the effect of recording and reporting system on data quality of primary health care in Banjarbaru City. This research uses observational analysis using quantitative method in 8 (eight) primary health care in Banjarbaru City. The sample in this study were 241 patients, 33 health workers in the recording reporting and observation of medical record documents. Sampling of patients in each primary health care based on accidental proportional sampling. Data were analyzed using Chi square test and multinomial logistic regression analysis. The resulth of Chi Square test showed significant influence of reporting on reporting data quality (p <0.05) Multinomial logistic regression test showed no significant effect of recording and reporting on data quality (p> 0,05)